2016
DOI: 10.1111/1754-9485.12429
|View full text |Cite
|
Sign up to set email alerts
|

Perforating arteries of the thigh: An anatomical and radiological study

Abstract: As in other parts of the body, textbook descriptions of anatomical structures may not be reflected consistently in vivo. However, the perforating branches of the profunda femoris demonstrate a predictable topographical relationship to palpable bony landmarks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…Farouk et al () reported a constant number of four perforating arteries in all of the 40 legs they investigated. Our data show that their number can vary between two and seven, which was also discussed by Dissanayake et al (). On the other hand, Lipshutz () reported the possibility of two to five and Adachi () of only two to four perforating arteries.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Farouk et al () reported a constant number of four perforating arteries in all of the 40 legs they investigated. Our data show that their number can vary between two and seven, which was also discussed by Dissanayake et al (). On the other hand, Lipshutz () reported the possibility of two to five and Adachi () of only two to four perforating arteries.…”
Section: Discussionsupporting
confidence: 89%
“…Although some authors tried to fix the origin of the perforating arteries (Siddharth et al, ; Dissanayake et al, ), or their passage near the body of the femur (Farouk et al, ), the present investigation showed that the position of the individual perforating arteries is quite variable. It was not possible to identify hotspots of these arteries, neither for their origin nor for their passage.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations